Complementary and Alternative Medicine Use in Modern Obstetrics: A Survey of the Central Association of Obstetricians & Gynecologists Members. (July 2017) - Babbar, Shilpa; Williams, Karen B.; Maulik, Dev
The use of complementary and alternative medicine during pregnancy is currently on the rise. A validated survey was conducted at the Central Association of Obstetrician and Gynecologists annual meeting to evaluate the knowledge, attitude, and practice of general obstetricians and gynecologists and maternal-fetal medicine specialists in America. We obtained 128 responses: 73 electronically (57%) and 55 via the paper survey (43%). Forty-five percent reported personally using complementary and alternative medicine and 9% of women respondents used complementary and alternative medicine during pregnancy. Overall, 62% had advised their patients to utilize some form of complementary and alternative medicine in pregnancy. Biofeedback, massage therapy, meditation, and yoga were considered the most effective modalities in pregnancy (median [semi-interquartile range] = 2 [0.5]). Maternal-fetal medicine specialists were significantly more likely to disagree on the use of complementary and alternative medicine for risk reduction of preterm birth compared to obstetricians and gynecologists ( P = .03). As the use of complementary and alternative medicine continues to rise in reproductive-age women, obstetricians will play an integral role in incorporating complementary and alternative medicine use with conventional medicine.